2021
DOI: 10.1177/00220345211029266
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing of 5 Families with Severe Early-Onset Periodontitis

Abstract: Periodontitis is characterized by alveolar bone loss leading to tooth loss. A small proportion of patients develop severe periodontitis at the juvenile or adolescent age without exposure to the main risk factors of the disease. It is considered that these cases carry rare variants with large causal effects, but the specific variants are largely unknown. In this study, we performed exome sequencing of 5 families with children who developed stage IV, grade C, periodontitis between 3 and 18 y of age. In 1 family,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Notably, in a study aimed at identifying causative mutations for severe adolescent‐onset periodontitis, a highly deleterious missense mutation (rs1404827864, CADD = 29, gnomAD genomes European MAF = 0.00003) within HMCN1 was detected by whole exome sequencing. This mutation was found in two affected children with stage III/IV‐C periodontitis that was diagnosed at adolescent age (Richter et al, 2022), but not in a healthy sibling. Taken together, it is conceivable that HMCN2 is an important factor in human tissue (re‐)modelling and may play a role in periodontal tissue repair and wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in a study aimed at identifying causative mutations for severe adolescent‐onset periodontitis, a highly deleterious missense mutation (rs1404827864, CADD = 29, gnomAD genomes European MAF = 0.00003) within HMCN1 was detected by whole exome sequencing. This mutation was found in two affected children with stage III/IV‐C periodontitis that was diagnosed at adolescent age (Richter et al, 2022), but not in a healthy sibling. Taken together, it is conceivable that HMCN2 is an important factor in human tissue (re‐)modelling and may play a role in periodontal tissue repair and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…rs11084095 was also among the associated variants in the present meta‐GWAS. Furthermore, within SIGLEC5 , a deleterious rare frameshift mutation (rs149243374, CADD = 24.0, ExAc EUR MAF = 0.00455) was found by whole exome sequencing in a family of adolescent stage III, grade C periodontitis (Richter et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We found that 3 miRNAs each regulated a periodontitis risk gene. These were CPEB1 ( Rhodin et al 2014 ), ABCA1 ( Richter et al 2022 ), and ATP6V1C1 ( Munz et al 2019 ), which were regulated by hsa-miR-130a-3p, hsa-miR-144-3p, and hsa-miR-144-5p, respectively. In addition, CPEB1 and ATP6V1C1 were among the 10 most downregulated genes after miRNA upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…So far, functional alteration of NOD2 caused by each mutation has not been revealed. Most recently, exosome sequencing of children who developed stage IV, grade C periodontitis identified mutations in gene loci of CTSC , TUT7 , PADI1 , FLG , ABCA1 , GLT6D1 , and SIGLEC5 [28] . Thus, the genetic background responsible for AP has mostly been clarified.…”
Section: Genetic Factors Of Periodontitismentioning
confidence: 99%